Autonomous Vehicles and Public Health: Literature Review. (June 2017) - Rojas-Rueda, David; Nieuwenhuijsen, Mark; Khreis, Haneen
Abstract : Background: Autonomous Vehicles (AVs) have the potential to transform mobility and society in positive and negative ways that will have an impact on health and well-being. A general framework, outlining key pathways by which AVs will impact public health is currently lacking. Methods: A review of the scientific literature was conducted to identifying the pathways of AVs technology to potential health determinants and outcomes. Information was strategically mapped in an effort to develop policy recommendations aimed at defining the health benefits and risks associated with AVs. Results: AVs have been associated to two main models 1) private AVs (private ownership) and 2) AVs sharing system (analogous to ride share and/or Uber). AVs can be also classified in two different groups according their engine technology: A) Fossil fuels AVs and B) Electric AVs. Compared to conventional vehicles, AVs are predicted to reduce traffic incidents and associated fatalities and injuries. In addition, vulnerable populations such as the elderly and disabled may realize greater independence and social interaction. At the same time, it is probable that private ownership AVs will not only support, but lead to an increase in the amount of land dedicated to new roadway infrastructure, thus encouraging dependency on private vehicles and community sprawl; increase congestion, trip length, energy consumption, air and noise pollution; and counteract efforts to promote mixed-use facilities, uptake of transit, and active travel options. Decreasing the overall number of cars on the roadways through AVs sharing system could have the opposite impacts of private AVs. In addition, relinquishing private vehicle ownership increases the amount of disposable personal income resulting in greater quality of life. On other hand fossil fuel AVs could increase air pollution and noise emissions. In contrast electric AVs could reduce the exhaust traffic-related air pollution and noise emissions, but increase the population exposure to electromagnetic fields. Conclusions: Even with the trade-offs and many unknown consequences of AVs as an evolving technology, it has the potential to positively impact the overall health of society if is properly regulated and managed by the authorities and the society. AVs could improve public health through improvements to safety, access, personal utility and further improvements in the environment when individuals abandon ownership of private vehicles and fossil fuels.